A meta-analysis comparing 18F-FLT PET with 18F-FDG PET for assessment of brain tumor recurrence. Issue 7 (July 2015) - Li, Zhaoping; Yu, Yue; Zhang, Huanhuan; Xu, Guifa; Chen, Liyong
Abstract : Objective: The purpose of this systematic meta-analysis was to evaluate the diagnostic accuracy of 3′-deoxy-3′- 18 F-fluorothymidine ( 18 F-FLT) PET for the assessment of glioma recurrence and compare it with that of 18 F-fluorodeoxyglucose ( 18 F-FDG) PET. Methods: The authors electronically and manually searched for studies from 1948 to 2014 that evaluated the diagnostic accuracy of 18 F-FDG or 18 F-FLT PET for glioma recurrence. The primary results of sensitivity, specificity, and diagnostic odds ratio (DOR) were summarized using the random-effects model. Summary receiver operating characteristic (ROC) curves and its area under the curve (AUC were used to summarize the overall diagnostic accuracy. Statistical analysis was performed with the software STATA (version 11.0). Results: Twenty-four studies that included a total of 799 patients were included in the meta-analysis. The pooled sensitivity, specificity, DOR, and summary ROC AUC for the overall diagnostic accuracy of 18 F-FDG PET were 0.78 (95% CI 0.69–0.85), 0.77 (95% CI 0.66–0.85), 12 (95% CI 6–22), and 0.84 (95% CI 0.81–0.87), respectively. The pooled sensitivity, specificity, DOR, and summary ROC AUC for the overall diagnostic accuracy of 18 F-FLT PET were 0.82 (95% CI 0.51–0.95), 0.76 (95% CI 0.50–0.91), 15 (95% CI 4–56), and 0.85 (95% CI 0.81–0.88), respectively. Metaregression analysis showed that year of publication, male proportion, average age, and blinding review did not affect the test performance statistically significantly (all P >0.05). Conclusion: This meta-analysis indicates that PET by using 18 F-FLT has a moderately better overall accuracy for diagnosing glioma recurrence compared with that by using 18 F-FDG. Video abstract: http://links.lww.com/NMC/A41 Abstract : Supplemental Digital Content is available in the text.